Differences and trend changes of the maximum hand grip force in selected karate male in function of age: a pilot study - Koropanovski, N.; Dopsaj, M.; Mudric, M. (FIS communications in Physical Education, Sport and Recreation, 2016)
The hand grip test is relatively simple and doesn`t demand efforts characteristics for other motor tests. Beside the fact that hand grip force do not has direct influence on karate competitive achievement, it could be the indicator of athletes condition. The goal of this work was to model developmental trends in contractile characteristics in terms of the maximum force of the flexor muscles of the fingers on the basis of data from the hand grip test collected in a sample of male karate athletes recruited from the Republic of Serbia`s male karate training system. The sample consisted of 66 male participants organized into age categories: senior, junior, cadet, hope and pioneer. The contractile properties of hand grip muscle force were indexed using maximal muscle force for the right, the left and summarized the right and the left hand. Trends in variables as a function of age were defined using linear regression and by mathematical modeling method using dependency functions. There is a statistically significant difference between all observed groups in all Fmax variables, while there were no differences between hopes and cadets, and cadets and juniors also. Trend of increase in maximal right, left and summary value of left and right hand grip force in function of different age groups - selected group of R Serbia karate athletes, is 83.78 N, 80.71 N and 164.49 N in every age category in regard to absolute level of expressed force, respectively. The defined model in this study can be accepted as statistically reliably and on the level of initial testing. Future studies in this area should be directed on accessing of karate training effects in regard to trends of basic and specific abilities changing.